TRANSRACIAL ADOPTION AND ITS EFFECTS TO CHILDREN’S PSYCHOLOGY IN STEVE WHAN’S NOVEL BULLETS ON THE BUND (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2013)
This study analyzed the effects of transracial adoption toward children’s psychology. Transracial adoption means the joining of racially different parents and children together in adoptive families (Hall and Steinberg, 2003:1). There are positive and negative effects of transracial adoption which are still debated. This final project was aimed at analyzing how transracial adoption affects children’s psychology as reflected in Bullets on the Bund. The objectives of the study is answering the statements of problem: first, how transracial adoption is revealed in Bullets on the Bund; second, what are the effects of trasracial adoption toward children’s psychology as reflected in the novel; third, what are the suggested ways to overcome effects of trasracial adoption toward children’s psychology. I employed Steve Whan’s novel Bullets on the Bund as the object of this study. This study is a descriptive qualitative study with Psychology of Literature as the approach. It is descriptive qualitative since the data of the study are in the form of words, phrases, sentences, narrations and dialogues and I did not employ computation. The data were gained by reading the novel thoroughly, identifying, inventorying, and classifying; then the analysis was done by selecting and explaining. There are several findings as the investigation result. First, transracial adoption is revealed implicitly in the novel since the plot of the novel is about the adventure of transracially adopted child. Second, transracial adoption can affect adopted children’s psychology. The psychological effects of transracial adoption found in the novel are: children may suffer feeling of loss, rejection, grief, and confusion of identity. Third, there are some ways to overcome the effects of transracial adoption, they are: letting children know the truth, support group, developing sense of racial identity. However, adoptive family support is the most important role to overcome the effects of transracial adoption toward children psychology. Adoptive parents love and care can decrease the negative effects of transracial adoption. Whereas the openness of children feeling toward situation they face eases the family to take an action to overcome the psychological effects of transracial adoption. For the next researcher, I suggest to analyze loss cultural identity issue in transracial adoption.